When x = 7
Plug in 7 for x
-----------------------------------------------------------------------------------------------------------------
f(x) = (3/(x + 2)) - √(x - 3)
f(7) = (3/(7 + 2)) - √(7 - 3)
-----------------------------------------------------------------------------------------------------------------
First simplify each parenthesis.
7 + 2 = 9
7 - 3 = 4
f(7) = (3/9) - √(4)
-----------------------------------------------------------------------------------------------------------------
Simplify. Divide 3 with 9, and root 4
f(7) = 1/3 - 2
-----------------------------------------------------------------------------------------------------------------
Subtract
f(7) = 1/3 - 2
f(7) = 1/3 - 6/3
f(7) = - 5/3
-----------------------------------------------------------------------------------------------------------------
Answer: f(7) = -5/3
-----------------------------------------------------------------------------------------------------------------
hope this helps